2007
DOI: 10.1026/0012-1924.53.4.218
|View full text |Cite
|
Sign up to set email alerts
|

Validierung einer deutschsprachigen Version des Body Image Avoidance Questionnaire BIAQ

Abstract: Zusammenfassung. Ziel dieser Studie ist die Validierung der deutschsprachigen Übersetzung des Body Image Avoidance Questionnaire (BIAQ). Der 19-Item-Fragebogen ist ein Instrument zur Selbstbeurteilung von Verhaltensweisen, die häufig bei Körperbildstörungen auftreten und mit Sorgen hinsichtlich der physischen Erscheinung einhergehen können. Er erfasst insbesondere körperbezogenes Vermeidungs- und Kontrollverhalten. Die deutschsprachige Version des BIAQ wurde an einer Stichprobe von n = 296 Studentinnen (KG) un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
2
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 14 publications
0
31
2
11
Order By: Relevance
“…The original questionnaire contained four factors: clothing, social activities, eating restraint, and grooming and weighing (Maïano, Morin, Monthuy-Blanc, & Garbarino, 2009;Rosen et al, 1991). Other studies have found two or three factor models (Campana, Tavares, da Silva, & Diogo, 2009;Legenbauer, Vocks, & Schütt-Strömel, 2007;Lydecker, Cotter, & Mazzeo, 2014;Riva & Molinari, 1998). Internal consistency reliability (Cronbach's = .64 -.89) and test-retest reliability (r = .64 -87) vary across studies (Legenbauer et al, 2007;Lydecker et al, 2014;Maïano et al, 2009;Riva & Molinari, 1998;Rosen et al, 1991).…”
Section: Participants Completed the Following Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The original questionnaire contained four factors: clothing, social activities, eating restraint, and grooming and weighing (Maïano, Morin, Monthuy-Blanc, & Garbarino, 2009;Rosen et al, 1991). Other studies have found two or three factor models (Campana, Tavares, da Silva, & Diogo, 2009;Legenbauer, Vocks, & Schütt-Strömel, 2007;Lydecker, Cotter, & Mazzeo, 2014;Riva & Molinari, 1998). Internal consistency reliability (Cronbach's = .64 -.89) and test-retest reliability (r = .64 -87) vary across studies (Legenbauer et al, 2007;Lydecker et al, 2014;Maïano et al, 2009;Riva & Molinari, 1998;Rosen et al, 1991).…”
Section: Participants Completed the Following Measuresmentioning
confidence: 99%
“…Other studies have found two or three factor models (Campana, Tavares, da Silva, & Diogo, 2009;Legenbauer, Vocks, & Schütt-Strömel, 2007;Lydecker, Cotter, & Mazzeo, 2014;Riva & Molinari, 1998). Internal consistency reliability (Cronbach's = .64 -.89) and test-retest reliability (r = .64 -87) vary across studies (Legenbauer et al, 2007;Lydecker et al, 2014;Maïano et al, 2009;Riva & Molinari, 1998;Rosen et al, 1991). The BIAQ is correlated with measures of eating disorder psychopathology, body shape and size, social physique anxiety, and self-esteem, and participants with bulimia nervosa had greater scores compared to controls (Maïano et al, 2009;Rosen et al, 1991).…”
Section: Participants Completed the Following Measuresmentioning
confidence: 99%
“…Given controversy regarding factor structure of the BIAQ within research, the current study used a total score, rather than specific subscales to provide a more robust measure of body image avoidance. However, in general, research has reported the BIAQ to be a mostly valid and psychometrically sound instrument, with internal consistencies ranging between .64 and .80 (Maïano, Morin, Monthuy-Blanc, & Garbarino, 2009) and good temporal stability across ages and gender (Legenbauer et al, 2007). The BIAQ has been reported to discriminate well between clinical and nonclinical populations, with individuals diagnosed with bulimia nervosa obtaining higher scores than control groups (Campana et al, 2012. Eating Pathology.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked to complete the Body Image Avoidance Questionnaire (BIAQ; Rosen, Srebnik, Saltzberg, & Wendt, 1991). The BIAQ is a self-report measure of behavioral tendencies, which have been identified to accompany body image disturbance (Legenbauer, Vocks, & Schütt-Strömel, 2007). The BIAQ consists of 19 items, divided into four factors: clothing, social activities, eating restraint and grooming and weighing (Rosen et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Other researchers report adequate internal consistency for alternate forms of the BIAQ, α = .64-.87 (Legenbauer, Vocks, & Schütt-Strömel, 2007;Maïano et al, 2009). Multiple studies report good test-retest reliability, with reliability coefficients of r = .64 -.87 (Legenbauer, Vocks, & Schütt-Strömel, 2007;Maïano et al, 2009). Test makers assert that the BIAQ displays good convergent validity.…”
Section: Behavioral Bidmentioning
confidence: 99%